2018
DOI: 10.1016/j.foodchem.2018.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterol crystallisation within bulk and dispersed triacylglycerol matrices as influenced by oil droplet size and low molecular weight surfactant addition

Abstract: Phytosterols can lower LDL-cholesterol and are frequently used by the functional food industry. However, little is known regarding how phytosterol crystallisation can be controlled, despite solubilised phytosterols having improved bioaccessibility. This study investigates phytosterol crystallisation in bulk milk fat and in model dairy emulsion systems at two average droplet sizes, 1.0 and 0.2 µm. The effect of lecithin and monoacylglycerol addition on phytosterol crystallisation for both emulsion and bulk syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Decreases in particle size have been observed previously with phytosterol enrichment in milk fat-based emulsions (Zychowski et al, 2016). Statistically significant decreases in particle size have been observed previously with phytosterol enrichment in milk fat-based emulsions (Zychowski et al, 2018;Zychowski et al, 2016). The overall droplet size distribution ranged from 0.1 to 16.4 µm (Fig.…”
Section: Particle Sizementioning
confidence: 64%
See 3 more Smart Citations
“…Decreases in particle size have been observed previously with phytosterol enrichment in milk fat-based emulsions (Zychowski et al, 2016). Statistically significant decreases in particle size have been observed previously with phytosterol enrichment in milk fat-based emulsions (Zychowski et al, 2018;Zychowski et al, 2016). The overall droplet size distribution ranged from 0.1 to 16.4 µm (Fig.…”
Section: Particle Sizementioning
confidence: 64%
“…Emulsions were prepared by homogenization with an APV 1000 homogenizer (SPX flow, Germany) at 300 bar pressure for 1 pass at 60°C. Higher pressures or more passes were not employed within this study as more intense treatments yielded smaller droplets, which were unsuitable for microscopic evaluation (Zychowski et al, 2018). Emulsions were allowed to statically cool and were stored at 20-25°C with 0.1% sodium azide added to the final emulsion.…”
Section: Preparation Of Emulsionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remarkable stability profile of the emulsions was also attributed to the surface activity of β-sitosterol that reduces the interfacial free energy at the interface, and thus renders some degree of stability to the resulting emulsion system [23]. Furthermore, in studies performed by Chen et al (2016) and Zychowski et al (2018), phytosterols have been found to improve the overall stability of the oil in water emulsion over time [24,25]. Figure 2 represents the chemical stability of the NLCs at different temperatures over time in terms of their β-sitosterol content.…”
Section: Physical and Chemical Stabilitymentioning
confidence: 99%